2020
DOI: 10.1088/1361-6668/ab617b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electromechanical behaviors in Cu-stabilized GdBCO coated conductor tapes using high-cycle fatigue tests at 77 K and related fractographic observations

Abstract: In applications employing high-temperature superconducting conductors, various cyclic loading (fatigue) conditions produced by mechanical, thermal, or periodic electromagnetic forces are inevitable. Applying coated conductor (CC) tapes under fatigue loading conditions is expected to critically affect the long-term reliability of its superconducting performance. Most studies evaluating the mechanical and electromechanical characteristics use quasi-static uniaxial tensile tests. Few have focused on the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Note that before etching the YBCO layer in this sample, no cracks were observed on the surface of the YBCO layer other than the cutting cracks. Figure 8(a) shows that significant cracks formed by loading are randomly distributed in the YBCO layer at almost perpendicular to the loading direction, observed using SEM after etching the YBCO layer for 80 s. Except for a few cutting cracks (labelled with red arrows in figure 8(a)) propagated inward at the slit edge, which is similar to the fatigue tests at 77 K [28], most cracks formed directly in the YBCO layer. Then the initiation of these cracks was investigated.…”
Section: Propagation Modes Of Crackssupporting
confidence: 61%
See 2 more Smart Citations
“…Note that before etching the YBCO layer in this sample, no cracks were observed on the surface of the YBCO layer other than the cutting cracks. Figure 8(a) shows that significant cracks formed by loading are randomly distributed in the YBCO layer at almost perpendicular to the loading direction, observed using SEM after etching the YBCO layer for 80 s. Except for a few cutting cracks (labelled with red arrows in figure 8(a)) propagated inward at the slit edge, which is similar to the fatigue tests at 77 K [28], most cracks formed directly in the YBCO layer. Then the initiation of these cracks was investigated.…”
Section: Propagation Modes Of Crackssupporting
confidence: 61%
“…For these samples, no a-axis grains are observed and only non-superconducting phase particles are randomly distributed at its edge. However, compared with the edge of 12 mm wide YBCO-CCs without microcracks seen in figure 2(a), it is inevitable that microcracks at ∼ 40 • relative to the edge of conductor were introduced in 3 mm wide YBCO-CCs during the cutting of the samples [24,26,28], as shown in figure 2(b). Therefore, in order to avoid the influence of a-axis grains, the 3 mm wide cut samples of YBCO-CCs (labelled as B in figure 1(d)) were chosen for the following experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…609 MPa is the limit for 4 mm wide tape, and 679 MPa is the limit for 12 mm wide tape. Through fractographic studies, the electrical fatigue strength of a CC tape is discovered to be considerably influenced by the fracture behaviour in the SC layer, whereas the mechanical fatigue strength is mainly driven by the substrate [3]. At room temperature and 77 degrees Celsius, the monotonic tensile stress-strain curve for YBCO coated conductors were measured.…”
Section: Cycles)mentioning
confidence: 99%
“…The normal stress sensitivity coefficient and limit factor are k and f, respectively. By setting σmax = 669 MPa, σmin = 66.9 MPa, and R (stress ratio) = 0.1, these values can be calculated [3]. It may be observed that, fig.…”
Section: Theorymentioning
confidence: 99%